2018
DOI: 10.1177/0271678x18799176
|View full text |Cite|
|
Sign up to set email alerts
|

Phosphorus spectroscopy in acute TBI demonstrates metabolic changes that relate to outcome in the presence of normal structural MRI

Abstract: Metabolic dysfunction is a key pathophysiological process in the acute phase of traumatic brain injury (TBI). Although changes in brain glucose metabolism and extracellular lactate/pyruvate ratio are well known, it was hitherto unknown whether these translate to downstream changes in ATP metabolism and intracellular pH. We have performed the first clinical voxel-based in vivo phosphorus magnetic resonance spectroscopy (P MRS) in 13 acute-phase major TBI patients versus 10 healthy controls (HCs), at 3T, focusin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 88 publications
(140 reference statements)
0
9
0
Order By: Relevance
“…Increased glycolytic flux in the wake of TBI and ATP production may underlie this finding ( Jalloh et al, 2015 ). Similarly, Stovell et al (2020) found a decline in ATP during the acute phase of TBI and hypothesized that this reduction stems from neurons undergoing energy failure. However, this decrease has also been found in stroke, which may suggest that ATP is a biomarker for CNS injury or other types of tissue injury more generally.…”
Section: Discussionmentioning
confidence: 96%
“…Increased glycolytic flux in the wake of TBI and ATP production may underlie this finding ( Jalloh et al, 2015 ). Similarly, Stovell et al (2020) found a decline in ATP during the acute phase of TBI and hypothesized that this reduction stems from neurons undergoing energy failure. However, this decrease has also been found in stroke, which may suggest that ATP is a biomarker for CNS injury or other types of tissue injury more generally.…”
Section: Discussionmentioning
confidence: 96%
“…As such, we did not acquire follow-up MRI in all subjects and the analyses of the possible relationship between early metabolic derangements and structural outcome presented are illustrative of how future studies could address this issue. Future sequential imaging studies incorporating MRI and spectroscopy, 59 diffusion tensor imaging and multi-tracer PET ( 15 O, 18 F-FDG, and SV2A) 60 could delineate evidence of pan-necrosis, cortical atrophy and selective neuronal loss related to early metabolic derangements, and correlate these with functional deficits resulting in poor outcome post TBI.…”
Section: Discussionmentioning
confidence: 99%
“…Common biomarkers quantified in the brain include choline (a substrate for cellular membrane synthesis), N-acetylaspartate (NAA, a neuronal metabolite), myo-inositol (a glial metabolite), mobile lipids that originate from small isotopically tumbling microdomains embedded within the plasma membrane or stored in cytoplasmic intracellular lipid droplets (increased with higher levels of apoptosis and necrosis), neurotransmitters such as glutamate and GABA, antioxidants such as glutathione, biochemical byproducts such as lactate, and more [ 64 , 65 , 67 ]. Previously, 31P-MRS was commonly used because it allowed for labeling of substrates of the tricarboxylic acid cycle (TCA) cycle, including pyruvate and ATP [ 68 ]. Early in its history, use of MRS surged to aid in the diagnosis of brain neoplasms, demyelinating conditions, hypoxic–ischemic encephalopathy, and inherited metabolic disorders, and more recently it has been increasingly used in the diagnosis and management of TBI.…”
Section: Mr Spectroscopy (Mrs)mentioning
confidence: 99%
“…One study demonstrated that NAA, myo-inositol, and neurotransmitter concentrations were correlated with cognitive outcomes after pediatric TBI [ 71 ]. 31P-MRS has been used to study brain alkalosis after TBI, and such changes were associated with an unfavorable outcome [ 68 ]. In pediatric nonaccidental trauma patients, NAA:creatine and NAA:choline ratios from 1H-MR spectra were significantly associated with poor neurologic outcomes [ 72 ].…”
Section: Mr Spectroscopy (Mrs)mentioning
confidence: 99%